A case report on a rare presentation of Aeromonas hydrophila - Kambhampati, Nikhil Teja; Kurupath, Vasant Pazhayannoor; Chandra, Subhash; Menon, Abhishek C. (International Journal of Research in Medical Sciences, 2022)
The genus Aeromonas is a member of the family Vibrionaceae. Aeromonas hydrophila is a water-dwelling, gram-negative rod-shaped bacterium, associated with diarrheal illness and less commonly, bone and soft tissue infections, especially among immunocompromised patients. Here we reported a rare presentation of A. hydrophila causing septicemia, septic arthritis, and osteomyelitis in an immunocompetent patient. A 35-year-old female, known hypothyroidism, presented with low back pain for one and half months and left side hip pain radiating to the left lower limb for one month. While in the hospital, she subsequently developed overwhelming sepsis secondary to septic arthritis and osteomyelitis. Which was secondary to a multidrug-resistant strain of A. hydrophila. Despite broad-spectrum antibiotics and aggressive surgical management, she had a recurrence of the infection. Aeromonas species infection in both immunocompetent and immunocompromised patients may result in high morbidity and mortality. This organism is highly virulent and multidrug-resistant. So early diagnosis and early administration of antibiotics would give better outcomes.